Signatures of post-zygotic structural genetic aberrations in the cells of histologically normal breast tissue that can predispose to sporadic breast cancer - Forsberg, Lars A.; Rasi, Chiara; Pekar, Gyula; Davies, Hanna; Piotrowski, Arkadiusz; Absher, Devin; Razzaghian, Hamid Reza; Ambicka, Aleksandra; Halaszka, Krzysztof; Przewoźnik, Marcin; Kruczak, Anna; Mandava, Geeta; et al. (Genome Research, 2015)
Sporadic breast cancer (SBC) is a common disease without robust means of early risk prediction in the population. We studied 282 females with SBC, focusing on copy number aberrations in cancer-free breast tissue (uninvolved margin, UM) outside the primary tumor (PT). In total, 1162 UMs (1–14 per breast) were studied. Comparative analysis between UM(s), PT(s), and blood/skin from the same patient as a control is the core of the study design. We identified 108 patients with at least one aberrant UM, representing 38.3% of cases. Gains in gene copy number were the principal type of mutations in microscopically normal breast cells, suggesting that oncogenic activation of genes via increased gene copy number is a predominant mechanism for initiation of SBC pathogenesis. The gain of ERBB2, with overexpression of HER2 protein, was the most common aberration in normal cells. Five additional growth factor receptor genes (EGFR, FGFR1, IGF1R, LIFR, and NGFR) also showed recurrent gains, and these were occasionally present in combination with the gain of ERBB2. All the aberrations found in the normal breast cells were previously described in cancer literature, suggesting their causative, driving role in pathogenesis of SBC. We demonstrate that analysis of normal cells from cancer patients leads to identification of signatures that may increase risk of SBC and our results could influence the choice of surgical intervention to remove all predisposing cells. Early detection of copy number gains suggesting a predisposition toward cancer development, long before detectable tumors are formed, is a key to the anticipated shift into a preventive paradigm of personalized medicine for breast cancer.
10.1101/gr.187823.114